Understanding the propensity of wild predators to illegal poison baiting. (1st August 2012) - Márquez, C.; Vargas, J. M.; Villafuerte, R.; Fa, J. E.; Gompper, Matthew; Fritz, Hervé
Abstract In many parts of the world, illegal poisoning of wild predators has increased abruptly in recent decades. Birds of prey and carnivores have been targeted directly or indirectly if these are perceived to impact game species or domestic animals. Non‐target species have experienced widespread declines, even local extinctions, as the result of illegal use of poisoned bait. In this study, we used data on detected poisoning events in the southern Spanish region of Andalusia to measure the influence of extrinsic and intrinsic variables on poisoning propensity of 18 wild predator species. Extrinsic factors affecting a species being poisoned were those related to the predicted coverage of poisoning events and how this overlapped with the distribution range of each species. To achieve this, we mapped areas of high 'favourability' of poisoning, as well as areas favourable for the species. Intrinsic factors that could increase a species' chances of consuming poisoned bait were related to how much a species depended on scavenging for food, whether it lived in groups, pairs or solitary, and on its sedentariness (whether migratory or sedentary). For each species, we calculated an index of potential spatial conflict between the distribution of poisoning events and the species' most favourable natural areas. To assess a species' intrinsic likelihood for consuming poisoned bait, we derived an index from the species' feeding habits, its sociality and sedentariness. Finally, by combining the extrinsic and extrinsic indices, we produced a general index of propensity to poisoning. We show that vultures and the red kite (Milvus milvus) among the raptors had the highest propensity of being poisoned, while the Iberian grey wolf (Canis lupus signatus), red fox (Vulpes vulpes) and Eurasian badger (Meles meles) were more prone among the carnivores. With our method managers can measure vulnerability of species to poisoning and prioritize them in a clear spatial context.